Predictors of willingness to participate in COVID-19 clinical trials among Black and Latino adults - Christine M. Weston; Elizabeth L. Andrade; Wuraola Olawole; Monica Guerrero Vazquez; Hailey Miller; Sarah C. Stevens; Cyd Lacanienta; Nancy Perrin; Mark C. Edberg; Thomas A. Mellman; Yvonne Bronner; Roger Clark; et al. (Journal of Clinical and Translational Science)
Abstract